(untitled) (Tzintzun, Revista de Estudios Históricos, 2023)
In 1668, the commissioner of the Inquisition in the Philippine Islands, José de Paternina, imprisoned and later sent Governor Diego de Salcedo to New Spain. After the conflict that this action generated, the Council of the Indies and the Council of the Supreme Inquisition had to intervene. The objective of this text is to review how the historiography analyzed the case and present some new considerations from the analysis of the file that contains the investigation carried out by the Court of the Inquisition of Mexico. The hypothesis that is exposed is that the form of government of the Hispanic Monarchy caused these conflicts among its different government institutions and, at the same time, had the capacity to resolve them without actually causing major conflicts.